Investigating the importance of non-financial determinants of owning or leasing industrial real estate in Gauteng - Muchengwa, Dorica Daka (My University, 2018)
Corporate real estate is required by firms to operate business and this can either be owned or leased. Either option requires substantial amounts of money. Despite this fact most studies conducted have focussed on tangible corporate assets in general and not corporate real estate in particular, the reason put forward being that this asset type has diverse intangible aspects which makes the own or lease equation a complex one. South Africa is the second largest economy on the continent and has a real estate market rivalling that of European countries by size; these facts are reason enough to support investigating the real estate market in detail. Gauteng Province accounts for 34.4% of the country’s GDP and 23% of this is from the industrial sector. This study, which is based on a 2011 UK study by Barkham and Park, sought to establish whether non-financial factors play a key role in the decision to own or lease industrial real estate in Gauteng Province. The study used an empirical approach using Thematic Network analysis to explore the non-financial determinants of owning or leasing industrial real estate from data obtained from 4 firms. Findings reveal that both financial and non-financial determinants are considered in the LVB decision for industrial CRE in Gauteng. Ranking of these factors showed that 3 of the four respondents ranked the non-financial ones first followed by some financial ones. It is suggested that further research be conducted to cover a larger population i.e. industrial firms in the major cities with a large industrial presence country wide. Additionally one which includes different firm sizes and a mixed method for data collection and analysis.
A research Report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Property Development and Management, September 2018
Keywords: Real property--South Africa; Commercial real estate; Real estate business--South Africa--Finance